A community evaluation of Parent-Child Interaction Therapy for children with prenatal substance exposure. (September 2020) - Egan, Ryan; Wilsie, Carisa; Thompson, Yutian; Funderburk, Beverly; Bard, Elizabeth
Highlights: Parent-Child Interaction Therapy is effective for substance-exposed archival sample. Treatment improved parent-rated child behavior and therapist-observed parent skills. Attrition for the treatment was high and predicted mostly by minority status. Maternal polysubstance use appears unrelated to child treatment response. Abstract: Children with prenatal substance exposure (PSE) often have behavior problems, but few studies have demonstrated that behavior therapy can be effective for these children. The current study evaluated the efficacy of Parent-Child Interaction Therapy (PCIT) for improving behavior problems in a sample of 116 children with PSE using archival data from a Midwestern PCIT clinic. Analyses included mean comparisons of pre- and post-treatment measures of child and parent behavior, prediction of drop-out from treatment, and evaluation of the potential complicating effects of PSE on treatment response. Results indicate that treatment effects of PCIT for children with PSE appear similar to the outcomes observed elsewhere in the PCIT literature. There was no indication that maternal polysubstance use alters child response to treatment. Attrition was high, but similar to other community trials of PCIT. The current study lends support to the use of PCIT for children with PSE who have behavior problems.